Advances in Health Management - Comite, Ubaldo (IntechOpen, 2017)
The production of healthcare services had been out of the business, organizational, and technological dynamic that continually revolutionized the production of all other goods and services for a long time. Nowadays, this marginality has ceased as the need for healthcare is rising. Healthcare is now at the center of attention influenced by the never-ending demand of medical technology and substantial resource scarcity that imposes substantial organizational and entrepreneurial innovations. One decisive challenge that has emerged from such a situation is the management of healthcare processes, in the broad sense: healthcare professionals are called upon to demonstrate their ability to cope with complex problems because they are characterized in an institutional, ethical, organizational, and economic sense. With its eight chapters in a single segment, this book makes it possible to realize the specific nature of the problem. Its multidimensionality and the original approach are contributed and harmonized by scholars belonging to different disciplines.